Generation of hydroxyl radicals and singlet oxygen by particulate matter and its inorganic components. (July 2018) - Mikrut, Magdalena; Regiel-Futyra, Anna; Samek, Lucyna; Macyk, Wojciech; Stochel, Grażyna; van Eldik, Rudi
Abstract: Particulate matter (PM) can strongly affect redox biochemistry and therefore induce the response of the immune system and aggravate the course of autoimmune diseases. Nanoparticles containing transition metal compounds possessing semiconductor properties (TiO2, ZnO) may act as photocatalysts and accelerate the generation of reactive oxygen species (ROS) and reactive nitrogen species (RNS). In this study, the NIST standard reference material, SRM 1648a, has been analyzed in terms of this consideration. Organic compounds present in SRM 1648a were removed by cold oxygen plasma treatment. Samples of SRM 1648a with removed organic content (<2% of organic carbon, <1% of nitrogen) were obtained within 2 h of this treatment. The treatment did not affect the morphology of the powder. The reference material and PM2.5 collected in Kraków are composed of smaller particles and nanoparticles forming aggregates. The efficiency of (photo)generation of hydroxyl radicals and singlet oxygen was compared for original and organics-free samples. The analyzed samples showed the highest activity towards ROS generation when exposed to UV-vis-NIR light, moderate under UV irradiation, and the lowest in dark. Data collected in the present study suggest that the organic fraction is mostly responsible for singlet oxygen generation, as almost twice higher efficiency of 1 O2 generation was observed for the original NIST sample compared to the material without the organic fraction. However, particulate matter collected in Kraków was found to have a five times higher activity in singlet oxygen generation (compared for original NIST and Kraków dust samples). Graphical abstract: Image 1 Highlights: Organic components of particulate matter were removed by plasma. (Photo)generation of hydroxyl radicals by inorganic components was confirmed. Irradiated and non-irradiated samples of dust generate singlet oxygen. Efficiency of 1 O2 generation is enhanced by organic components of the dust. Abstract : Separation of organic and inorganic content of the NIST standard reference material, SRM 1648a, as well as of real PM2.5 samples collected in Kraków, enabled assessment of their role in the (photo)generation of reactive oxygen species.